MENCARI KEBEBASAN BEREKSPRESI: PENYEBAB REMAJA MEMILIKI "SECOND ACCOUNT" PADA APLIKASI INSTAGRAM - Nur Hasanah Harahap; Muhammad Alridho Lubis; Abdillah Basit; Indah Mahmuda; Rizka Rahmah Gita; Rohmawati Rohmawati; Zhava Livia Syahrani (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2026)
The phenomenon of second accounts on the Instagram application is a phenomenon that includes behavioral changes in social media users, especially in adolescents who are encouraged to have more than one account on the platform. The main objective of this research is to identify and understand the factors that encourage teenagers to have second accounts on social media platforms, especially on Instagram. The research method used in this study is a descriptive qualitative approach. This approach was chosen to gain an in-depth understanding of the phenomenon of second accounts on the Instagram application carried out by teenagers and the reasons behind teenagers' need for freedom of expression through the second account. The results of this study highlight the complexity of the second account phenomenon on Instagram, especially among adolescent girls aged 16 to 24. The study found that the factors behind teenagers' decision to have a second account include the need for privacy and security, self-identity exploration, and peer influence. The use of a second account allows teens to separate public content from private content shared with a limited circle, reveal aspects of themselves that may not be revealed on the main account, and express themselves more freely.